The Influence of Parenting Patterns on Stunting Incidence Among Toddlers at Puskesmas Pantoloan, Palu City - Bangkele, Elliyane; Sumarni, Sumarni; Miranti, Miranti; Nurjannah, Sitti; Tobanta, Bertha Anastacia; Suarayasa, Ketut (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Poor parenting in the family is one of the causes of inadequate nutritional intake, contributing to stunting. Stunting is a chronic malnutrition condition occurring in the first 1000 days of life, leading to delays in brain and physical development. According to the Ministry of Health, stunting is defined as a z-score less than -2SD and severe stunting as less than -3SD. Objectives: To determine the influence of parental parenting on the incidence of stunting in toddlers at the Pantoloan Community Health Center, Palu City. Methods: This case-control study involved 144 toddlers (72 stunting cases and 72 non-stunting controls) selected through purposive sampling. The total population was 947 toddlers. Data were analyzed using the Chi-square test. Results: There was no significant relationship between the type of parenting style and stunting incidence (P = 0.335, OR = 1.600). Similarly, no significant relationship was found between parenting methods and stunting incidence (P = 0.085, OR = 1.183). Conclusions: Parental parenting style and methods were not significantly associated with stunting incidence among toddlers at the Pantoloan Community Health Center, suggesting the need to explore other contributing factors.